Role of Microvesicles From Bone Marrow Mesenchymal Stem Cells in Acute Pancreatitis. Issue 9 (October 2016) - Yin, Guojian; Hu, Guoyong; Wan, Rong; Yu, Ge; Cang, Xiaofeng; Xiong, Jie; Ni, Jianbo; Hu, Yanling; Xing, Miao; Fan, Yuting; Xiao, Wenqin; Qiu, Lei; et al.
Abstract : Objectives: Mesenchymal stem cells (MSCs) have shown an obvious protective effect on acute pancreatitis (AP). The purpose of the present study was to analyze the effect of bone marrow MSC-derived microvesicles (bmMSC-MVs) on AP and explore the underlying mechanisms. Methods: Bone marrow MSCs and bmMSC-MVs were isolated from Sprague-Dawley rats. Cerulein-induced mild AP (MAP) and sodium taurocholate-induced severe AP (SAP) were used as AP models in vivo and in vitro. Pancreatic injury was evaluated by measuring serum levels of amylase, lipase, chemokines, and interleukins, and by pancreatic histology, reverse transcription-polymerase chain reaction, Western blotting, and immunohistochemistry. The effects of bmMSC-MVs on the survival rates of pancreatic acinar cells in vitro were also assessed. Results: Bone marrow MSC-MVs attenuated acute pancreatic injury in MAP and SAP by regulating IL-1α, IL-6, and TNF-α, and dramatically attenuated the nuclear translocation of NF-κB p65 in MAP and SAP. Bone marrow MSC-MVs improved the survival rates of pancreatic acinar cells in MAP and SAP models in vitro. Conclusions: Bone marrow MSC-MVs played a protective role in AP by reducing the levels of proinflammatory cytokines and regulating the nuclear translocation of NF-κB p65. Bone marrow MSC-MVs could be developed as a strategy for the clinical treatment of SAP.